생태주의 음악과 인문학 강의 운영 방안 - 황혜영(Hwang, Hyeyoung); 김혜진(Kim, Heyjin) (교양교육연구, 2020)
이 연구는 음악 전공과 인문학 전공 두 교수자가 코티칭 강좌로 운영하는 음악과 인문학 수업에서2020학년도 1학기부터 새롭게 도입한 생태주의 주제 수업 사례를 분석하는 것을 목적으로 한다. 오늘날심각한 생태위기는 인간이 생태계의 다른 생명체나 자연을 도구와 수단으로 여기는 인간중심적 가치관에 기인한다고 볼 수 있다. 생태 위기를 극복하기 위해서는 인간의 이기주의적 인간중심사상과 무분별한자연 개발에 대한 반성과 실질적인 환경개선 방안 모색과 함께 보다 근본적으로 인간이 생태계 다른구성원들과 조화와 상생을 추구하는 생태적 가치관을 회복하는 것이 필요하다. 본 수업에서는 표층적 생태관과 심층적 생태관 두 관점에서 음악과 인문학에 접근해보고 자연 친화적인 시와 동요, 자연을 테마로 하는 음악 작품들을 감상하였다. 또한 2020년 급작스러운 코로나 19 사태로 사회적 거리두기를 해야 되는 상황에서 음악과 함께 오감을 활용하여 자연을 느껴보는 체험시간을 가지도록 오감마인드맵으로 자연 체험 소감과 느낌을 표현하도록 하였다. 학생들은 이 수업후의 설문에서 생태주의 테마 음악과 인문학 수업이 정서적인 회복을 도모하고 몸의 감각을 통해생태주의 사고를 갖는데 도움이 되었다고 의견을 주었다. 우리는 비대면 온라인 강의 수강 환경에서이러한 생태 체험 오감마인드맵 활동을 통해 학생들이 자신이 직접 선정한 음악을 감상하며 오감을열고 자연에 다가가는 체험에서 느낀 생생한 감각을 신선하고 독창적인 인상으로 묘사하고 있는 것을확인할 수 있었다. 자연친화적인 사고와 감성을 함양하고 자연에 가까이 다가가고자 한 것과 더불어코로나 위기 속에서 음악과 자연, 인문학적 성찰로 자아를 어루만져주는 기회를 가진 점에 이번 자연과가까워지는 생태주의 음악과 인문학 수업의 의의가 있다. The purpose of this study is to analyze classes conducted by two professors in the music major and the humanities major during the first semester of 2020, who introduced a new themes of ecological music and humanities. Today, the ecological crisis due to the damage to nature and environmental pollution is getting serious. The ecological crisis is attributed to human-centered values in which humans regard other lives in the ecosystem as merely tools and means. In order to overcome this crisis, it is necessary for us to reflect upon selfish, human-centered thoughts and the reckless development of nature, as well as to seek practical environmental improvement plans and solutions. Fundamentally, humans must restore ecological values that seek harmony and coexistence with other members of the ecosystem. In music and humanities classes, we first looked at the seriousness of the ecological crisis and environmental problems, and took time to reflect on ecological problems, all while listening to environmental music. Furthermore, while listening to nature-friendly music, we shared the ecological-oriented values which state humans should respect and live in harmony with other living organisms in the ecosystem listening to nature-friendly music. In consideration of the COVID-19 pandemic that began earlier this year, we guided the students to take the time to try to heal themselves while experiencing nature with spring-themed music. The two professors encouraged the students to create a five-sense mind map for the experience of feeling nature with music, thereby inducing an emotional recovery and promoting the reinforcement of ecological thinking. The significance of ecological music and humanities classes is that they try to cultivate nature-friendly thinking and sensibility, bring students closer to nature, and provide students the opportunity to touch emotions through music, nature, and reflection on the humanities. KCI Citation Count: 0